Transforming Laboratory Learning through Project-Oriented Laboratories: Challenges, Opportunities, and Recommendations for Science Education - Hidayat, Febrian Andi; Kaniawati*, Ida; Suhandi, Andi; Hernani, Hernani; Anakotta, Raisa; Ramadany, Lisa Dewi (Universitas Syiah Kuala, 2025)
Project-oriented laboratories (POLs) and project-based laboratories (PBLs) approaches have become important innovations in science education, providing more relevant learning experiences through real-world based projects. This study aims to evaluate the potential of POLs implementation in supporting science education integrated with sustainable development goals (SDGs) issues, particularly to develop creative ideas in solving environmental problems. In addition, this study also aims to identify the main challenges faced in the implementation of POLs and provide practical recommendations to optimize this approach. Through a systematic literature review based on Prisma 2020 guidelines, 34 articles from 1993 to 2024 were analyzed. The results showed that POLs are effective in improving students' technical, collaboration, and problem-solving skills. However, the integration of POLs with SDGs issues is still limited. Although some projects, such as the development of renewable energy systems, support SDG 7 (clean and affordable energy), most projects have not been strategically geared towards solving other global challenges, such as climate change mitigation (SDG 13) or waste management (SDG 12). The research identified key challenges in the implementation of POLs, including the need for technological infrastructure, intensive training for educators, and funding support. To maximize their impact, it is recommended that POLs actively integrate SDGs themes into project design and promote cross-disciplinary collaboration. This research confirms that POLs have great potential to support science education that not only results in academic achievement, but also tangible contributions to global sustainability